Leukotriene-mediated neuroinflammation, toxic brain damage, and neurodegeneration in acute methanol poisoning - Zakharov, Sergey; Kotikova, Katerina; Nurieva, Olga; Hlusicka, Jiri; Kacer, Petr; Urban, Pavel; Vaneckova, Manuela; Seidl, Zdenek; Diblik, Pavel; Kuthan, Pavel; Navratil, Tomas; Pelclova, Daniela (Clinical toxicology (Philadelphia, Pa.), 2017)
CONTEXT: The role of neuroinflammation in methanol-induced toxic brain damage has not been studied. OBJECTIVE: We studied acute concentrations and the dynamics of leukotrienes (LT) in serum in hospitalized patients with acute methanol poisoning and in survivors. METHODS: Series of acute cysteinyl-LT and LTB4 concentration measurements were performed in 28/101 hospitalized patients (mean observation time: 88 ± 20 h). In 36 survivors, control LT measurements were performed 2 years after discharge. RESULTS: The acute maximum (Cmax) LT concentrations were higher than concentrations in survivors: Cmax for LTC4 was 80.7 ± 5.6 versus 47.9 ± 4.5 pg/mL; for LTD4, 51.0 ± 6.6 versus 23.1 ± 2.1 pg/mL; for LTE4, 64.2 ± 6.0 versus 26.2 ± 3.9 pg/mL; for LTB4, 59.8 ± 6.2 versus 27.2 ± 1.4 pg/mL (all p < 0.001). The patients who survived had higher LT concentrations than those who died (all p < 0.01). Among survivors, patients with CNS sequelae had lower LTE4 and LTB4 than did those without sequelae (both p < 0.05). The LT concentrations increased at a rate of 0.4-0.5 pg/mL/h and peaked 4-5 days after admission. The patients with better outcomes had higher cys-LTs (all p < 0.01) and LTB4 (p < 0.05). More severely poisoned patients had lower acute LT concentrations than those with minor acidemia. The follow-up LT concentrations in survivors with and without CNS sequelae did not differ (all p > 0.05). The mean decrease in LT concentration was 30.9 ± 9.0 pg/mL for LTC4, 26.3 ± 8.6 pg/mL for LTD4, 37.3 ± 6.4 pg/mL for LTE4, and 32.0 ± 8.8 pg/mL for LTB4. CONCLUSIONS: Our findings suggest that leukotriene-mediated neuroinflammation may play an important role in the mechanisms of toxic brain damage in acute methanol poisoning in humans. Acute elevation of LT concentrations was moderate, transitory, and was not followed by chronic neuroinflammation in survivors.
Keywords: Leukotrienes; hydrogenuhličitany; methanol; mozek; nontraumatic brain injury; Cysteine; leukotrieny; Humans; neurodegenerativní nemoci; lidé středního věku; leukotrienes; kreatinin; Neuroinflammation; sequelae of poisoning; formiáty; Female; Inflammation; ethanol; výsledek terapie; brain damage; lidé; Blood Glucose; Creatinine; Poisoning; hospitalizace; zánět; cystein; Bicarbonates; Follow-Up Studies; ženské pohlaví; Hospitalization; Male; Middle Aged; laktáty; krevní glukóza; Brain; Treatment Outcome; Hydrogen-Ion Concentration; Methanol; methanol poisoning; Formates; otrava; Neurodegenerative Diseases; Ethanol; mužské pohlaví; koncentrace vodíkových iontů; Acute Disease; Lactates; akutní nemoc; následné studie